The explorers : a story of fearless outcasts, blundering geniuses, and impossible success - Dugard, Martin (Simon & Schuster, 2014)
In The Explorers, New York Times bestselling author Martin Dugard shares the rich saga of the Burton and Speke expedition. To better understand their motivations and ultimate success, Dugard guides readers through the seven vital traits that Burton and Speke, as well as many of history's legendary explorers, called upon to see their impossible journeys through to the end: curiosity, hope, passion, courage, independence, self-discipline, and perseverance. In doing so, Dugard demonstrates that we are all explorers, and that these traits have a most practical application in everyday life.